Negative Effects on Neurogenesis, Ovariogenesis, and Fitness in Sea Turtle Hatchlings Associated to ex situ Incubation Management - Unda-Díaz, Nancy M.; Phillips-Farfán, Bryan V.; Nava, Hector; Lopez-Toledo, Leonel; Murata, Chiharu; Lajud, Naima; Herrera-Vargas, Ma. Antonia; Arreola Camacho, Claudia A.; Torner, Luz; Fuentes-Farías, Alma L.; Meléndez-Herrera, Esperanza (Frontiers in Ecology and Evolution, 2022)
Sea turtle egg relocation and hatchery incubation (hereafter termed ex-situ incubation) is an effective strategy to protect clutches when in-situ egg incubation is not viable. Nevertheless, it negatively affects the ontogenesis of male gonads and brain areas homologous to the mammalian hippocampus, as well as body size and fitness. Thus, it is imperative to analyze the effects of ex-situ incubation on other developmental aspects and extend these observations to females. This work evaluated the effect of ex-situ management on neurogenesis (cell proliferation in the dorsal and medial ventricular zones, neuronal integration in the dorsomedial and medial cortices), ovary cell proliferation, body size (mass and length) and self-righting ability. Additionally, this study examined if the incubation microenvironment is different between in-situ and ex-situ nests and whether it could contribute to explain the biological traits. An analysis of principal components showed differences in biological variables of hatchlings between in-situ and ex-situ clutches, driven by contrasting temperatures and silt composition. Each biological variable was also analyzed with linear mixed models using in-situ vs. ex-situ clutches, abiotic variables and their interaction. Turtles from ex-situ clutches showed: 1) fewer proliferating cells in the dorsal and medial ventricular zones; 2) less mature neurons in the dorsomedial and medial cortices; 3) ovaries with a lesser number of proliferating cells; 4) lower body mass and length at emergence and 5) slower self-righting time. Together, the results suggest that ex-situ incubation in hatcheries is related to a slowing down of neurogenesis, ovariogenesis, body size and self-righting ability in hatchlings. Future studies should evaluate the effect of ex-situ incubation on cognitive and reproductive performance to understand the long-term consequences of altered organogenesis. These studies should also disentangle the differential contribution of egg movement, reburial, nesting environment and parental origin to development. This information would likely result in better conservation strategies for sea turtles.